(untitled) (International Conference on Economics, Business, and Management Research (ICEBMR), 2025)
Nglanggeran Ancient Volcano (Gunung Api Purba Nglanggeran) in Gunung Kidul, Yogyakarta, represents one of Indonesia’s most successful applications of Community-Based Tourism (CBT). Once a marginal agricultural area, the community transformed it into a globally recognized destination through participatory governance, cultural revitalization, and environmental stewardship. This article examines the strategies underpinning Nglanggeran’s success, focusing on community participation, local entrepreneurship, asset mobilization, and sustainability practices. Using a qualitative case study approach informed by secondary literature and policy reports, the analysis highlights how CBT and Asset-Based Community Development (ABCD) principles enabled local actors to achieve social, economic, and environmental outcomes. Findings indicate that Nglanggeran not only improved household income and employment opportunities but also preserved cultural heritage and restored degraded landscapes. This study contributes to sustainable tourism discourse by demonstrating how CBT can be scaled and adapted in rural contexts, offering policy lessons for Indonesia and beyond.